1988
DOI: 10.1111/j.1365-2427.1988.tb00456.x
|View full text |Cite
|
Sign up to set email alerts
|

Digestive ability of the freshwater crayfish Paranephrops zealandicus (White) (Parastacidae) and the role of microbial enzymes

Abstract: 1. Ingestion rate, assimilation efficiency and digestive enzyme activity were investigated in the New Zealand freshwater crayfish, Paranephrops zealandicus (White). Rates of ingestion of fresh and decaying Elodea canadensis Michx. were highly variable at 15°C and assimilation efficiency averaged 21%.2. Hepatopancreas extracts showed enzyme activity towards each of nine substrates tested; microcrystalline cellulose (MCC), carboxymethyl cellulose (CMC), cellobiose, amylose, pectin, mannan, laminarin, chitin and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0

Year Published

1993
1993
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(20 citation statements)
references
References 25 publications
0
20
0
Order By: Relevance
“…The S 13 C enrichment of P. zealandicus compared with known diet categories might be a result of micro-organisms in crayfish stomachs assimilating the ingested material and in turn being assimilated by the crayfish (Hicks 1997). In support of this, cellulase activity associated with bacteria has been reported in the stomach of P. zealandicus (Musgrove 1988), but the extent of enrichment is not known (Hicks 1997). Equally, the importance of terrestrial material to crayfish in these streams may be as a surface for the growth of fungi, diatoms, and bacteria (Momot 1995;Whitledge & Rabeni 1997).…”
Section: Missing Food-web Link(s)?mentioning
confidence: 49%
See 1 more Smart Citation
“…The S 13 C enrichment of P. zealandicus compared with known diet categories might be a result of micro-organisms in crayfish stomachs assimilating the ingested material and in turn being assimilated by the crayfish (Hicks 1997). In support of this, cellulase activity associated with bacteria has been reported in the stomach of P. zealandicus (Musgrove 1988), but the extent of enrichment is not known (Hicks 1997). Equally, the importance of terrestrial material to crayfish in these streams may be as a surface for the growth of fungi, diatoms, and bacteria (Momot 1995;Whitledge & Rabeni 1997).…”
Section: Missing Food-web Link(s)?mentioning
confidence: 49%
“…), terrestrial invertebrates (whole or exoskeleton, identified to class), aquatic moss, autochthonous plant material (other than moss), aquatic invertebrates (whole or exoskeleton, other than crayfish, identified to genus), crayfish, inorganic material, and unidentified material. The percentage of the total stomach volume that each food category comprised was determined using the points method of Musgrove (1988). A 5 mm 2 grid beneath the petri dish aided in estimation of volume.…”
Section: Stomach Content Analysismentioning
confidence: 99%
“…The invertebrate-microbe interaction may simply be that of predator-prey, where the invertebrate utilizes the microflora directly as a food source [33,38,39,74,91,106,111,121,156,227]. Synergism has also been documented, e.g., where invertebrates facilitate bacterial colonization by mechanically breaking down or concentrating organic material in fecal pellets [92], while microflora may precondition food material for ingestion by invertebrates [15,16,42,43,53,90,147]. Activities of invertebrates, such as bioturbation or production of bacteriocidal substances, may enhance or inhibit growth of microorganisms [4,6,26,145,210], while microbes have been reported to inhibit the activities of invertebrates, e.g., as active parasites or pathogens [1,13,19,31,32,47,65,69,70,78,94,99,154,200].…”
Section: Microbe-invertebrate Interactions In the Aquatic Environmentmentioning
confidence: 99%
“…The term "resident" has often been used too loosely. Many authors suggest that bacteria are residents but do not provide conclusive evidence [147,203]. Populations of gut bacteria have been interpreted as residents simply because they are comparatively stable.…”
Section: Types Of Associations Between Aquatic Invertebrates and Theimentioning
confidence: 99%
See 1 more Smart Citation